A configurational approach to servitization : review and research directions - Kohtamäki, Marko; Henneberg, Stephan C.; Martinez, Veronica; Kimita, Koji; Gebauer, Heiko (INFORMS, 2019)
By acknowledging the full complexity of the phenomenon of servitization and its manifold drivers and outcomes, we extend the current literature through a configurational perspective, the aim of which is to understand the interplay between the drivers (conditions) that lead to certain equifinal outcomes of servitization. The present study aims to take stock of the servitization literature by utilizing the contingency theory of strategy as our foundational theory and the strategy–structure–environment approach as our primary framework to systematically review and analyze the identified configurational servitization studies. We identify commonalities and gaps in the literature, and we set directions for future research.
Keywords: servitization; product–service systems (PSS); configurational approach; typological approach; strategy–structure–environment fit; systematic review; fi=Johtaminen ja organisaatiot|en=Management and Organization|